2014
DOI: 10.1017/s1368980013003285
|View full text |Cite
|
Sign up to set email alerts
|

Waist-to-height ratio, inflammation and CVD risk in obese children

Abstract: Objective: To evaluate the association between waist-to-height ratio (WHtR) and specific biomarkers of inflammation, CVD risk and endothelial dysfunction in prepubertal obese children. Design: Prospective, multicentre case-control study matched by age and sex. Setting: Children were recruited between May 2007 and May 2010 from primarycare centres and schools in three cities in Spain (Cordoba, Santiago de Compostela and Zaragoza). Subjects: Four hundred and forty-six (223 normal weight and 223 obese) Caucasian … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
42
2
5

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 45 publications
(57 citation statements)
references
References 33 publications
8
42
2
5
Order By: Relevance
“…The presence of low-grade inflammation in obese childrenthat appeared in this studywas evaluated by measuring serumconcentrationsof CRP and IL6,as both showed a highly significant difference compared to the non-obese children and a very strong positive correlation with each other and with HOMA-IR and BMI.In agreement with thisJiménez et al [31],Sonya et al [32],Olzaet al [33], andValle et al [34]; all affirmed that the levels of these inflammatory markers are elevated in prepubertal obese children and that are associated with insulin resistance with the subsequent possibility of development of diabetes and cardiovascular disease. Additionally, Oliveira et al [35] agreed this finding and added that CRP is strongly related with metabolic syndrome and its components including insulin resistance in obese youth.Semiz et al also approved this finding and stated that CRP correlated with BMI and BP which are risk factors for coronary heart disease, supporting the relationship between obesity, inflammation and atherosclerosis [36].IL-6 is an inflammatory cytokine that stimulates the hepatic productionof CRPthis can explain the state ofinflammationassociated with obesity, and could mediate, at least partially,obesity-related insulin resistance [37].…”
Section: Discussionsupporting
confidence: 86%
“…The presence of low-grade inflammation in obese childrenthat appeared in this studywas evaluated by measuring serumconcentrationsof CRP and IL6,as both showed a highly significant difference compared to the non-obese children and a very strong positive correlation with each other and with HOMA-IR and BMI.In agreement with thisJiménez et al [31],Sonya et al [32],Olzaet al [33], andValle et al [34]; all affirmed that the levels of these inflammatory markers are elevated in prepubertal obese children and that are associated with insulin resistance with the subsequent possibility of development of diabetes and cardiovascular disease. Additionally, Oliveira et al [35] agreed this finding and added that CRP is strongly related with metabolic syndrome and its components including insulin resistance in obese youth.Semiz et al also approved this finding and stated that CRP correlated with BMI and BP which are risk factors for coronary heart disease, supporting the relationship between obesity, inflammation and atherosclerosis [36].IL-6 is an inflammatory cytokine that stimulates the hepatic productionof CRPthis can explain the state ofinflammationassociated with obesity, and could mediate, at least partially,obesity-related insulin resistance [37].…”
Section: Discussionsupporting
confidence: 86%
“…Scientific evidence shows that WHtR was strongly associated with abdominal fat measured by advanced imaging techniques such as computed tomography and magnetic resonance imaging [18]. Several studies of sensitivity and specificity demonstrated the WHtR as a method to use for identifying childhood overweight, obesity, and tracking of inflammatory and cardiometabolic risk in 6-to 16-year-old children [4,6,7,[10][11][12].…”
Section: Discussionmentioning
confidence: 99%
“…Several anthropometric and body composition indexes have been used to measure obesity and to assess the risk of metabolic and cardiovascular diseases [3,4].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations